Synthesis of fully substituted 3-formyl-4-iodofurans via a gold(I)-catalyzed oxidation/1,2-alkynyl migration/cyclization/Iodination cascade - Wang, Tao; Shi, Shuai; Rudolph, Matthias; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2014)
A highly efficient gold(I)-catalyzed cascade reaction for the synthesis of fully substituted 3-formyl-4-iodofurans has been developed. Mechanistic investigations indicate a reaction pathway that involves a direct iodination reaction of the organogold intermediate via functionalization of the AuC(sp2) bond, instead of a direct iodination of the 3-formylfurans.
Gesehen am 07.08.2020